Medical and surgical nurses' knowledge of Continuity of care - Amaliyah, Riski; Dewi, Wan Nishfa; Tampubolon, Nurhannifah Rizky (University of Muhammadiyah Malang, 2024)
Introduction: Nurses play a significant role in implementing continuity of care to reduce readmission risk. Nurses’ knowledge about continuity of care is essential to ensure that continuity of care occurs consistently. Objectives: This study aims to determine nurses’ knowledge about continuity of care. Methods: This study used a descriptive research design. The study sample comprised 95 nurses in the medical and surgical inpatient room of Arifin Achmad Hospital, who were selected using the total sampling technique. The study variables include nurses’ knowledge about continuity of care measured using a questionnaire developed by the researcher and used after validity testing. The data analysis employed for this study was descriptive analysis, which represents data in frequency and percentage. Results: The findings of this study depict that respondents' age mainly was at 19-44 years (87,4%), most of the respondents were female (78,9%), most with a diploma of nursing education background (50,5%), working experience more than 12 years (51,6%), and the majority of respondents had sufficient knowledge about continuity of care (68,4%). Conclusions: Nurses' knowledge of continuing care found in this study is adequate. These findings provide an overview of nurses' potential contribution and readiness to implement continuity of care to reduce the readmission rate. The implications of nursing knowledge on continuing care in practice will provide comprehensive and coordinated care to improve the quality of care that can improve patient’s quality of life.